The Role and Involvement of Orang Laut of Johor-Riau during the Era of Traditional Malay Kingdom: (Peranan dan Penglibatan Orang Laut Johor-Riau semasa Era Kerajaan Melayu Tradisional) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
The Orang Laut of Johor-Riau played a significant role in the early establishment of traditional Malay kingdoms. A qualitative approach together with document and manuscript analysis were applied to answer research questions using primary sources such as documents and manuscripts. The study was also supported by secondary sources in the form of books, journals and articles. The findings show that the Orang Laut of Johor-Riau were the pillars of strength and glory from the time of the Srivijaya Empire up to the time of the kingdoms of Melaka (Malacca) and Johor-Riau. Changes in these polities due to the fragmentation of the Johor-Riau kingdom in the late 17th century affected the reciprocal relationship between the Orang Laut and the Malay kingdoms. The conclusion that this study draws is that the changes in these polities marginalized the Orang Laut of Johor-Riau. The implications of this study are that the changes in these polities apparently affected people who did not move in tandem with such changes.Keywords: Orang Laut of Johor-Riau, Srivijaya, Melaka/Malacca, traditional Malay kingdoms, civilization